2019
DOI: 10.1093/ofid/ofz346
|View full text |Cite
|
Sign up to set email alerts
|

Sofosbuvir Add-on to Ribavirin Treatment for Chronic Hepatitis E Virus Infection in Solid Organ Transplant Recipients Does Not Result in Sustained Virological Response

Abstract: Ribavirin is effective for treating immunocompromised patients with chronic hepatitis E virus infection. However, ribavirin treatment is not always successful. We describe 3 solid organ transplant recipients treated with sofosbuvir and ribavirin after failing ribavirin monotherapy. Complete elimination of hepatitis E virus could not be achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…Sofosbuvir has been proposed as an alternative treatment method for chronic hepatitis E. Although it seems to have some efficacy in vitro, 78 only two out of seven patients described in case reports achieved a SVR 79‐86 . Combination of peg‐IFN and RBV has been described in three patients, resulting in SVR in one patient 87‐89 .…”
Section: Discussionmentioning
confidence: 99%
“…Sofosbuvir has been proposed as an alternative treatment method for chronic hepatitis E. Although it seems to have some efficacy in vitro, 78 only two out of seven patients described in case reports achieved a SVR 79‐86 . Combination of peg‐IFN and RBV has been described in three patients, resulting in SVR in one patient 87‐89 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the use of SOF monotherapy in those patients who are not eligible for RBV use has demonstrated a lack of efficacy [66]. Furthermore, the lack of efficacy also has been reported in the second-line treatment approach in transplant-recipient patients [67]. Consequently, the use of SOF is not recommended for the therapy of HEV infection.…”
Section: Discussionmentioning
confidence: 99%
“…No other antiviral therapy is presently known to be effective against a chronic HEV infection. Sofosbuvir was shown to have antiviral activity against HEV in vitro [192] but had limited efficacy in HEV-infected patients [193][194][195][196][197][198][199][200]. A recent pilot study of nine patients (seven for whom ribavirin had previously failed) given sofosbuvir (400 mg/day) for 24 weeks found that their HEV viremia decreased, but was not cleared.…”
Section: Treatmentmentioning
confidence: 99%